The viral etiology of acute febrile illness of in Dhaka, Bangladesh in the year of 2017 - Arifa Akram; AKM Muraduzzaman; Manjur Hossain Khan Jony; Sharmin Sultana; Ahmed Nawsher Alam; Meerjady Sabrina Flora; Tahmina Shirin (Journal of Clinical Virology Plus, 2022)
Background: This is sometimes a challenge to identify the etiologies of acute febrile illnesses (AFI) due to non-specific clinical presentation as well as limited availability of diagnostic facilities. Bangladesh is very much suitable for vector borne viral infections like Dengue, Chikungunya and Zika due to hot and humid climate. Method: In 2017 during the period of April to November there was an outbreak of febrile illness in Dhaka city, the capital of Bangladesh. With the aim to explore the situation Institute of Epidemiology, Disease Control and Research (IEDCR) took an initiative to investigate the etiology of febrile illness. Sixteen hundred and thirty two patients with history of acute onset of fever with or without arthalgia and rash, who attended to IEDCR,were tested for Dengue, Chikungunya and Zika by multiplex PCR. Results: Among them 66%, 7% and 0.4% were positive for Chikungunya, Dengue and co-infected with both pathogens respectively. Dengue virus positive serum samples were further analyzed for serotyping and found re-emergence of DEN-3 in the circulation along with existing serotypes DEN-1 and DEN-2. Conclusion: Considering the climatic condition and existence of domestic and peri-domestic setup in Bangladesh correlates with persistent mosquito breeding and survival as well as transmissibility of vector borne viral diseases. Thus continuous surveillance is required from public health point of view for prevention and control of arboviral diseases in Bangladesh.